Application of Iodine as a Catalyst in Aerobic Oxidations: A Sustainable Approach for Thiol Oxidations - Lijun Wang; Lingxia Chen; Zixuan Qin; Ke Ni; Xiao Li; Zhiyuan Yu; Zichen Kuang; Xinshu Qin; Hongxia Duan; Jie An (Molecules, 2023)
Iodine is a well-known oxidant that is widely used in organic syntheses. Thiol oxidation by stoichiometric iodine is one of the most commonly employed strategies for the synthesis of valuable disulfides. While recent advancements in catalytic aerobic oxidation conditions have eliminated the need for stoichiometric oxidants, concerns persist regarding the use of toxic or expensive catalysts. In this study, we discovered that iodine can be used as a cheap, low-toxicity catalyst in the aerobic oxidation of thiols. In the catalytic cycle, iodine can be regenerated via HI oxidation by O2 at 70 °C in EtOAc. This protocol harnesses sustainable oxygen as the terminal oxidant, enabling the conversion of primary and secondary thiols with remarkable efficiency. Notably, all 26 tested thiols, encompassing various sensitive functional groups, were successfully converted into their corresponding disulfides with yields ranging from >66% to 98% at a catalyst loading of 5 mol%.